2019
DOI: 10.1177/0095327x19845030
|View full text |Cite
|
Sign up to set email alerts
|

Communities Serve: A Systematic Review of Need Assessments on U.S. Veteran and Military-Connected Populations

Abstract: Military veterans and their families face a multiplicity of challenges once they transition from service. Even though more American private and public-sector organizations are engaged in studying the needs of veterans and their families through need assessments, few assessments are comprehensive analyses of the challenges they face. This systematic review of 61 need assessments from 2007-2018 in the United States summarizes findings on 18 veterans issues. While most studies addressed issues relating to accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…37,38 Over 45,000 military-focused non-profit organizations outside the VA also provide support to this population, often with limited coordination across organizations that provide complementary services. 31 Responding to the multitude of services available to Veterans and military families, 7,[39][40][41] the AmericaServes Program was established to build, sustain, and evaluate regional, coordinated networks of public and private organizations supporting US military Veterans. 42,43 Designed to integrate services across systems and improve service navigation, 29 regional AmericaServes Coordination Centers facilitate a hub and spoke model of health and social service delivery with participating organizations serving the same region.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Over 45,000 military-focused non-profit organizations outside the VA also provide support to this population, often with limited coordination across organizations that provide complementary services. 31 Responding to the multitude of services available to Veterans and military families, 7,[39][40][41] the AmericaServes Program was established to build, sustain, and evaluate regional, coordinated networks of public and private organizations supporting US military Veterans. 42,43 Designed to integrate services across systems and improve service navigation, 29 regional AmericaServes Coordination Centers facilitate a hub and spoke model of health and social service delivery with participating organizations serving the same region.…”
Section: Introductionmentioning
confidence: 99%
“…1 As the largest single health care provider in the country, the Veterans Health Administration (VHA) offers veterans broad-ranging services encompassing physical, behavioral, and social health domains. However, little is known about LGBTQ+ veterans' utilization of health care generally or VHA and military health plans specifically, 2 particularly compared to non-LGBTQ+ veterans. LGBTQ+ veterans have experienced a long history of discrimination in military service and in VHA, 3,4 which may contribute to discomfort in seeking care at VHA.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of Veteran needs assessments found a scarcity of reports addressing rural Veterans (Van Slyke & Armstrong, 2020). Further research is required to understand the needs of this population, including how to address obstacles that prevent rural Veterans experiencing housing instability from engaging in services.…”
Section: Introductionmentioning
confidence: 99%